Quality of internet-based information on obstetric anesthesia (Annals of Medical Research, 2021)
Aim: The internet is one of the most frequently used tools to reach up to actual information. In the field of health, patients frequently search for treatment options and outcomes over the internet. In this study, the quality and reliability of the data on obstetric anesthesia were investigated.Material and Methods: The ten most frequently searched keywords for obstetric anesthesia and the first 30 search results for each word were analyzed with JAMA Benchmark Criteria and Discern score. The web sites that emerged as servers were divided into 5 classes as anesthesia associations and academic papers, public institutions, private hospitals/clinics, news and forums/personal blogs. Results: The average DISCERN score of all sites was calculated as 29.75±7.04. The quality of the information provided on the internet about obstetric anesthesia was evaluated as poor. The most common results for our keywords were provided by private hospitals (27.8%). Web sites linked to public institutions were the last to provide information (2.2%). Treatment options and benefits are the most clearly mentioned issues, while risks and treatment failure are the least addressed. According to the JAMA benchmark criterion, the majority of sites had up-to-date but unclear information.Conclusions: In obstetric anesthesia, the quality and reliability of the information provided on the internet are poor. It was concluded that the anesthesiology associations were not sufficiently involved on the internet in informing patients about obstetric anesthesia. Patients applying in health institutions should be advised that the information on the internet may not be reliable and that they should consult a specialist physician.Keywords: Obstetric anesthesia; internet-based information; DISCERN score; JAMA Benchmark criteria
Keywords: s for obstetric anesthesia and the first 30 search results for each word were analyzed with JAMA Benchmark Criteria and Discern score. The web sites that emerged as servers were divided into 5 classes as anesthesia associations and academic papers, public institutions, private hospitals/clinics, news and forums/personal blogs. br /Results: The average DISCERN score of all sites was calculated as 29.75±7.04. The quality of the information provided on the internet about obstetric anesthesia was evaluated as poor. The most common results for our s were provided by private hospitals (27.8%). Web sites linked to public institutions were the last to provide information (2.2%). Treatment options and benefits are the most clearly mentioned issues, while risks and treatment failure are the least addressed. According to the JAMA benchmark criterion, the majority of sites had up-to-date but unclear information.br /Conclusions: In obstetric anesthesia, the quality and reliability of the information provided on the internet are poor. It was concluded that the anesthesiology associations were not sufficiently involved on the internet in informing patients about obstetric anesthesia. Patients applying in health institutions should be advised that the information on the internet may not be reliable and that they should consult a specialist physician.br / Obstetric anesthesia; internet-based information; DISCERN score; JAMA Benchmark criteria